Gamifizierung mit BPMN - Morschheuser, Benedikt; Hrach, Christian; Alt, Rainer; Lefanczyk, Christoph (HMD : Praxis der Wirtschaftsinformatik, 2015)
During recent years the application of gamification to increase motivation of information technology use has gained great popularity in science and practice. Due to the novelty of the gamification phenomena only few concrete models and notations exist to gamify information systems. This article proposes an extension for BPMN and gamification process patterns, which were derived from various gamification use cases. The developed approach was evaluated in a practical use case and a structured expert survey. The findings indicate practical benefits for planning, communication and documentation of gamification projects.<br
Keywords: Gamification; BPMN; Prozesse; Sprache; Modellierung